Fungsi partai politik menurut pandangan Sosiologi Politik dalam masyarakat - Niken Tri Prasetyowati; Anita Trisiana; Dany Satria Aji (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
All layers of society are very familiar with this political forum. Especially before the election, volunteer candidates and political parties will flock to make supporting billboards to support a proposal from one of the parties. According to Law No. 2 of 2008 concerning Political Parties, is an organization consisting of a group of Indonesian citizens based on the aspirations and desires of members, society, state and state, as well as the political interests of all parties. Maintaining the integrity of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution. In general, a political party is a stable and neat organization consisting of a group of people who wish to have certain aspirations, ideals and ideology features. seeking power through elections to achieve alternative policies and plans. Therefore they have been compiled.